Autoantibodies to Tumor-Associated Antigens as Cancer Biomarkers - Belousov, P. V.; Kuprash, D. V.; Nedospasov, S. A.; Shebzukhov, Y. V. (Current Molecular Medicine, 2010)
Malignant tumors induce humoral immune response in cancer patients, although the incidence of such autoantibody responses against individual tumor-associated antigens (TAA) is rather low. To increase predictive value of TAA-recognizing autoantibodies as potential cancer biomarkers, TAAs should be combined into protein arrays. Here we review recent advances in the application of such arrays and summarize data concerning most promising antigens. We also review the methods of cloning TAA-recognizing autoantibodies, generation of human hybridomas and screening of recombinant human immunoglobulin libraries.
Keywords: Cancer